Performance in the establishment of a bond in the services ofattention to tuberculosis - Tânia Maria Ribeiro Monteiro de Figueiredo; Mayrla Lima Pinto; Maria Aparecida Alves Cardoso; Valkênia Alves Silva (Rev Rene)
The objective of this work was to investigate the performance in establishing the link between the professional and the tuberculosis patients treated in health services in Campina Grande/PB/Brazil. It is a descriptive and cross-sectional study, of quantitative approach. The study population consisted of 79 patients. For data collection, it was used an instrument that is a component of the Primary Care Assessment Tool. The data analysis was performed using the Program SPSS 13.0. 43,04% of the respondents were treated in the Reference Clinic and 56,96% in the Basic Unit of Family Health. The study subjects followed the same pattern: male in a productive age with low education. Regarding the creation of the bond, the two services had favorable performances. The study revealed satisfactory performance regarding the effectiveness of professional-patient relationship in both services that develop actions for the tuberculosis control.